Conductivity, magnetic and LPG sensing behavior of PANI/CaFe2O4 nano composites. Issue 1 (10th December 2021) - Anjum, Rehana; Husain, Jakeer; Reddy, Narsappa; Rani, D. Sharon Swaroopa; Radhika, G.
Abstract: CaFe2 O4 nanoparticles were successfully prepared by sol-gel method. Nanocomposites of PANI and CaFe2 O4 have been synthesized using the in situ polymerization method for different concentrations of nano CaFe2 O4 powder. The formation of polymer nanocomposite and changes in the structural and micro structural properties of the materials were investigated by X-ray diffractometry (XRD). The surface morphology of PANI – CaFe2 O4 nanocomposite was elucidated using Scanning Electron Microscopy and Transmission electron microscopy. AC conductivity studies of PANI – CaFe2 O4 composites for different wt% show thermally activated behavior. The conductivity was found to increase with the increase in temperature indicating the semiconducting behavior of all the compositions. Maximum conductivity was observed in 50 wt% of CaFe2 O4 in PANI. On exposure of the composites to LPG, increase in resistance was observed with the increase in gas concentration. Maximum sensitivity for gas sensing was observed in the composite of 50 wt% CaFe2 O4 in Polyaniline. The magnetic properties of PANI nanocomposites are larger at 50 wt% and decreases with decreasing the concentration of CaFe2 O4 nanoparticles in PANI composite.